Identity, the Manosphere, and Misogyny: Unpacking the Digital Pipeline - Analoui, Sara (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Child Development.; Advisor: Julie Dobrow.; Committee: Theo Klimstra, and Adam Gismondi.; Keywords: Developmental psychology, Mass communication, and Gender studies.